Integrative investigation on Hippocratea africana root: insights from cardio-protective, anti-oxidative stress activities, isolation, GC/MS, and pharmacological significance profiling - Edet Effiong Asanga; Kufre Uyo Noah; Jude Efiom Okokon; Chinedum Martins Ekeleme; Imaobong Etima Udoh; Augustine Bassey; Martin Osita Anagboso; Aniekeme Ndisa Inyang (BMC Complementary Medicine and Therapies)
Abstract Background Hippocratea africana root is scientifically used in cardiotoxicity treatment; therefore, this study was designed to validate this claims through the evaluation of its cardioprotective activity, isolation, and characterization of its constituents, as well as in silico profiling of these ligands against antioxidant enzymes. Methods Standard protocols were followed in the extraction, fractionation, isolation, characterization, evaluation of cardio-protective activity (marker enzymes, oxidative stress markers, and histological section), retrieval of target proteins (SOD, CAT, GPx, and GSH), ADMET, and docking studies. Column and thin layer chromatography as well as GC/MS aided the isolation and characterization of compounds; SWISSADME and ADMET lab 2 enhanced the evaluation of pharmacokinetic properties; PyRx for docking analysis; Biovia discovery studio and PyMol software for 2D and 3D visualization of the ligand–protein interactions. Results The root extract administration significantly (p < 0.05) reduced the serum levels of CK-MB, LDH, and troponin I that were elevated after doxorubicin administration; however, the levels of GSH, GST, SOD, GPx, and CAT that were decreased after doxorubicin administration were significantly (p < 0.05) elevated whereas the raised MDA level was reduced after treatment with the extract and fractions of the plant. Also, the histological sections in the extract-treated rats showed reductions in pathological features as compared with the negative control group. Moreover, the chemical pathological changes were consistent with histopathological observations suggesting marked cardio-protective potentials. Furthermore, the chromatographic analyses yielded bulked fractions {D3 (11 mg), E6 (25 mg), and E8 (21 mg)} and their GC/MS analyses revealed dihydroartemisinin; retinoic acid, methyl ester; α-thujene; α-terpinolene; 9,12,15-octadecatrienal; α-terpineol etc. with already reported antioxidant activities. These ligands (dihydroartemisinin; retinoic acid, methyl ester) obeyed Lipinski’s criteria, had remarkable pharmacokinetic profiles, and their docking analyses revealed that they modulated antioxidant enzymes with better binding affinities than vitamin C. Conclusion Given the demonstrated antidotal and cardioprotective properties of the plant root, it presents a promising candidate for mitigating doxorubicin-induced toxicities and could be effectively utilized as a supportive therapy in such contexts.